2006
DOI: 10.1038/sj.onc.1209713
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated cyclin E promotes p53 loss of heterozygosity and tumorigenesis in the mouse mammary gland

Abstract: Deregulation of cyclin E expression and/or high levels have been reported in a variety of tumors and have been used as indicators of poor prognosis. Although the role that cyclin E plays in tumorigenesis remains unclear, there is evidence that it confers genomic instability when deregulated in cultured cells. Here we show that deregulated expression of a hyperstable allele of cyclin E in mice heterozygous for p53 synergistically increases mammary tumorigenesis more than that in mice carrying either of these ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…For example, Fbw7 heterozygosity was found to accelerate tumorigenesis in p53 heterozygous, but not in p53 null mice, suggesting that the cooperativity resulted primarily from loss of p53 driven by Fbw7-associated genome instability, and that once p53 was mutated, Fbw7 loss was no longer a cooperating event (Mao et al, 2004). Similarly, p53 loss was suggested to be an early consequence of cyclin E transgene expression in a murine breast cancer model, again suggesting that p53 is the critical mutational target of cyclin E-induced instability (Smith et al, 2006). However, while p53-loss is likely to be an important consequence of the genetic instability caused by Fbw7 loss or cyclin E gain, several lines of evidence indicate that p53 function also directly suppresses cyclin E-and Fbw7-associated genetic instability.…”
Section: Scfmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, Fbw7 heterozygosity was found to accelerate tumorigenesis in p53 heterozygous, but not in p53 null mice, suggesting that the cooperativity resulted primarily from loss of p53 driven by Fbw7-associated genome instability, and that once p53 was mutated, Fbw7 loss was no longer a cooperating event (Mao et al, 2004). Similarly, p53 loss was suggested to be an early consequence of cyclin E transgene expression in a murine breast cancer model, again suggesting that p53 is the critical mutational target of cyclin E-induced instability (Smith et al, 2006). However, while p53-loss is likely to be an important consequence of the genetic instability caused by Fbw7 loss or cyclin E gain, several lines of evidence indicate that p53 function also directly suppresses cyclin E-and Fbw7-associated genetic instability.…”
Section: Scfmentioning
confidence: 88%
“…and aberrant cyclin E activity causes genetic instability and tumorigenesis (Spruck et al, 1999;Minella et al, 2002;Loeb et al, 2005;Smith et al, 2006). Many human cancers express high levels of cyclin E (Hwang and Clurman, 2005), and this is thought to directly contribute to cell transformation and tumor aggressiveness.…”
mentioning
confidence: 99%
“…In the absence of a functional Fbw7 pathway, caused either by mutating cyclin E at its CPDs or by deleting FBXW7, cyclin E activity is pathologically sustained throughout the cell cycle, leading to aberrant S-phase progression, delayed mitotic exit, and genome instability (21)(22)(23)(24). In vivo, impaired Fbw7-mediated cyclin E degradation causes increased cell proliferation and impaired maturation in a cell type-specific manner as well as increased tumorigenesis (21,(25)(26)(27). The developmental abnormalities associated with impaired Fbw7-mediated regulation in a cyclin E T74A T393A knock-in mouse model are especially pronounced in erythroid cell precursors, which exhibit hyperproliferation, increased apoptosis, and dysplastic morphologies (25).…”
mentioning
confidence: 99%
“…16,17 Although it has been suggested that excessive levels of cyclin E promote proliferation, the best evidence is that deregulation of cyclin E expression contributes to oncogenesis by causing genomic instability. [18][19][20] One potential mechanism for cyclin E deregulation during oncogenesis is through inactivation of the cyclin E degradation pathway. Indeed, it has been demonstrated that Cdc4 is frequently mutated in a broad spectrum of human cancers, leading to elevated levels and cell cycle deregulation of cyclin E. 9,18,21,22 It is likely therefore that some of the tumorigenic effects of Cdc4 mutation are mediated via cyclin E deregulation.…”
Section: Introductionmentioning
confidence: 99%